FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN DAERAH DENGAN BELANJA MODAL SEBAGAI VARIABEL MODERASI: (Studi Pada Provinsi Nusa Tenggara Timur Periode 2016-2020) - Amanda Yecci Noeng; Lilis Ardini; Kurnia (Politeknik Ganesha Medan, 2023)
This study aimed to examine some factors which influence the local financial performance, with capital expenditure as the moderating variable, in East Nusa Tenggara from 2016-up to 2020. The data in this study used the Budget Realization Report of Local Government in East Nusa Tenggara. Furthermore, the research was quantitative. The data analysis technique applied multiple linear regression; and Moderated Regression Analysis for testing moderating variables. As a result, the fiscal balance had a significant positive effect on local financial performance. However, both local-owned source revenue and economic growth had an insignificant effect on local financial performance. The capital expenditure strengthened the effect of local owned-source revenue on local financial performance, but it did not strengthen the fiscal balance as well as the economic growth. The study also revealed that the Local Government of East Nusa Tenggara applied supervision or control toward the assignments for their subordinates, in order to finish on time. Besides, they gave appreciation to the ones who succeed in doing the task given.